The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1002/maco.201609075
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation behavior of T91 steel in flowing oxygen‐containing lead‐bismuth eutectic at 500 °C

Abstract: T91 is considered as a possible structural material for lead‐bismuth eutectic (LBE) cooled reactors. However, one of the main issues is the compatibility of T91 with LBE. In this work, the corrosion tests of T91 were performed in flowing (1 m/s) oxygen‐controlled LBE (1–3 × 10−6 wt% O) at 500 °C for up to 5000 h. The results show that a three‐layer oxide scale forms at the interface of T91 and LBE, consisting of Fe3O4 (magnetite), Fe‐Cr spinel and an internal oxidation zone (IOZ). The growth kinetics of the ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Mechanisms: uniform oxidation (diamonds), uniform dissolution (circles), and locally enhanced dissolution (triangles). [92,101,115,117,172,180,181,183,185,187,[189][190][191][215][216][217]219,225,227,[230][231][232]234,[237][238][239][240]. Mechanisms: uniform oxidation (diamonds), uniform dissolution (circles), and locally enhanced dissolution (triangles).…”
Section: The Role Of Hlm Oxygen Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Mechanisms: uniform oxidation (diamonds), uniform dissolution (circles), and locally enhanced dissolution (triangles). [92,101,115,117,172,180,181,183,185,187,[189][190][191][215][216][217]219,225,227,[230][231][232]234,[237][238][239][240]. Mechanisms: uniform oxidation (diamonds), uniform dissolution (circles), and locally enhanced dissolution (triangles).…”
Section: The Role Of Hlm Oxygen Concentrationmentioning
confidence: 99%
“…HLMs: LBE, Pb, Bi, 36Pb-64Bi, 26Pb-74Bi. Data collected from Refs [92,101,115,117,172,180,181,183,185,187,[189][190][191][215][216][217]219,225,227,[230][231][232]234,[237][238][239][240]…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] In addition, Tian et al found that the shedding of the oxide layer plays an important role in the corrosion rate of steel in the LBE. 17 Recently, theoretical simulations were also conducted to obtain the corrosion information of steel and its oxides in the LBE. Recently, Xu et al investigated the adsorption of Pb, Bi and Au atoms and escape of Fe atoms from iron surfaces in liquid metals.…”
Section: Introductionmentioning
confidence: 99%
“…This option is not recommended for high temperature applications (above 500 • C) because the kinetics of oxide growth is fast. This would result in a thick and weakly adherent layer of oxide [45,46]. Thus, reduction in thermal conductivity, oxide spallation, and channel plugging are arising issues.…”
mentioning
confidence: 99%